2016
DOI: 10.1097/mjt.0000000000000254
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of Lobectomy on Immunologic Function Between Video-Assisted Thoracoscopic Surgery and Traditional Open Surgery for Non–Small-Cell Lung Cancer

Abstract: To compare the effects of lobectomy on immunologic function between video-assisted thoracoscopic surgery (VATS) and traditional open surgery (TOS) for non-small-cell lung cancer (NSCLC). A total of 80 patients with NSCLC were recruited from Liaoning Cancer Hospital & Institute between June 2013 and August 2014. The participators were grouped into VATS and TOS at random. The levels of C-reactive protein, serum amyloid A, interleukin (IL) 6, and IL-2R were detected before operation, 24 hours, and 72 hours after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…However, major surgery for cancer is known to induce lymphopenia and suppress lymphocyte function ( 18 ). Similar to previous studies ( 19 , 20 ), we demonstrated a significant decrease in peripheral lymphocyte subpopulations at 1 day postoperatively in all patients. IFN-γ production has been demonstrated to be well-correlated with various activities of lymphocytes and can be utilized as a symbol of lymphocyte function ( 17 ).…”
Section: Discussionsupporting
confidence: 91%
“…However, major surgery for cancer is known to induce lymphopenia and suppress lymphocyte function ( 18 ). Similar to previous studies ( 19 , 20 ), we demonstrated a significant decrease in peripheral lymphocyte subpopulations at 1 day postoperatively in all patients. IFN-γ production has been demonstrated to be well-correlated with various activities of lymphocytes and can be utilized as a symbol of lymphocyte function ( 17 ).…”
Section: Discussionsupporting
confidence: 91%
“…One hundred and sixty-nine reports of 145 studies met the predefined inclusion criteria and were included in the review. Seven studies were RCTs and included a total of 1,276 randomized patients, 19,94,111,126,168,169,171 and 138 studies including a total of 368,517 patients were nonrandomized cohort and case-control studies. In total the 145 studies included 369,793 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies including 332 patients measured quality of life using global QoL tools. 19,86,171 Pooled analysis showed significantly higher quality of life at 1 year in mVATS patients compared to open lobectomy (SMD 0.42; 95% CI, 0.20 to 0.64; P = 0.001). No heterogeneity was detected for this comparison (I 2 = 0%).…”
Section: Mvats Versus Open Lobectomymentioning
confidence: 99%
“…An immune response is involved during the lung surgery [28,29]. One-lung ventilation technique was consistently used during the pulmonary surgery.…”
Section: Discussionmentioning
confidence: 99%